CORPORATE TAX AVOIDANCE: HOW FINANCIAL HEALTH RESHAPES THE GAME - Nicklaus Stanley; Luky Patricia Widianingsih (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
Corporate tax avoidance has long been an ethical and social concern. Understanding what motivates firms to engage in such practices is crucial to maximizing national tax revenues. However, research on financial distress and corporate tax avoidance is commonly seen from the perspective of conventional theories, with the financial distress proxy being less accurate in the context of developing economies. Therefore, this research aims to gather empirical evidence regarding the effect of financial distress on corporate tax avoidance in Indonesia, specifically emphasizing the consumer cyclical sector. This study utilizes secondary data obtained from firms’ audited financial statements for the years 2019 to 2023, analyzed with the panel data regression approach. The results of this study indicate that financial distress significantly and negatively affects corporate tax avoidance. From the perspective of the risk compensation theory, financially distressed firms must respond to their dire situation by changing their behaviour, such as not committing to implementing risky tax avoidance activities. On the other hand, since financially healthy firms have a higher target level of risk, they would be more willing to engage in more tax since they have a ‘financial cushion’. Theoretically, the findings contribute to the accounting and taxation literature by integrating with the risk compensation theory. Practically, the results indicate that tax authorities are advised to scrutinize financially healthy firms more closely, as they tend to have a greater propensity to engage in corporate tax avoidance practices.